Dynamic stability performance of the Bataan thermal unit using analysis of eigenvalues of "A" matrix of linearized model - Eufemio, Napoleon C. (1971)
This paper describes the formulation of a linearized mathematical model of a one-machine system connected to an infinite bus through a transmission line. Using state space approach, the coefficient matrix or the so-called "A" matrix for the set of first-order differential equations describing the system is formed from equations and block diagrams that describe the system. The synchronous machine equations are expressed with regard to a synchronously rotating reference frame using a modified Park's transformation. The complete set of linearized equations includes excitation control and mechanical turbine control systems. The dynamic behavior of the system is investigated by looking at the eigenvalues of the "A" matrix and identifying the eigenvalue associated with the different circuits or parts of the system. One aspect of the study is to find the optimum setting of one parameter of the generator voltage regulator by noting the sensitivity of the eigenvalues to this parameter.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric power-plants.